Consumption effects of an electricity decarbonization policy: Hong Kong. (1st February 2018) - Woo, C.K.; Shiu, A.; Liu, Y.; Luo, X.; Zarnikau, J.
Abstract: This paper estimates the consumption effects of an electricity rate increase triggered by an electricity decarbonization policy's implementation. Underscoring its real-world relevance is the policy's net impact on CO2 emissions, the sum of (a) the supply-side impact attributable to using generation resources with low emissions to displace those with high emissions, and (b) the demand-side impact caused by energy consumption changes in response to the electricity rate increase. For Hong Kong, the changes in (b) are decreases in electricity consumption and increases in town gas consumption. Using a sample of monthly data for the period of 1981–2016, we document the low price responsiveness of Hong Kong's electricity and town gas demands by customer class (residential, commercial and industrial). Hence, the 40% projected electricity rate increase due to Hong Kong's adopted electricity decarbonization policy may only have a small demand-side impact on CO2 emissions. Finally, the electricity demands' low price responsiveness has two important policy implications. First, Hong Kong's demand-side-management should rely more on energy-efficiency improvements than price-induced consumption reductions. Second, restructuring Hong Kong's electricity industry to introduce wholesale competition should consider the potential for large electricity price spikes and market power abuse in connection to price-inelastic electricity demands. Highlights: Use monthly data to estimate Hong Kong energy demands' price responsiveness. Find retail demands for electricity and town gas to be highly price-inelastic. Measure the impact of a 40% electricity rate increase on retail energy consumption. Document a small demand-side impact on Hong Kong's annual CO2 emissions. Make policy recommendations for Hong Kong's electricity future.